Melampaui Transmisi: Konstruksi Teologi Komunikasi Pesan Religius di Era Digital - Titus Tunggul Simbolon; Jessica Caroline Charis (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2026)
The rapid development of the digital era over the last two decades demands a fresh reading of how religious messages are produced, distributed, and interpreted by modern society. This shift marks a transition from a linear, technical model of information transmission toward a more relational praxis of faith communion. This article examines communication theology as an analytical framework for understanding the complexity of religious messages within open, algorithmic digital spaces. Using a conceptual theoretical library research method, this study shows that communication theology transcends the technical limitations of conventional communication science by positioning religious messages as communicative acts imbued with theological meaning, spiritual experience, and relationality. This framework allows the analysis of religious messages to include an assessment of faith integrity, ethical theological responsibility, and the transformative impact of digital communication on communities of believers. Communication theology thus offers a balance between digital technological sophistication and the depth of faith substance so that religious communication remains relevant and capable of fostering authentic communion.   Abstrak Perkembangan era digital dalam dua dekade terakhir menuntut pembacaan ulang terhadap cara pesan religius diproduksi, disebarkan, dan dimaknai oleh masyarakat modern. Pergeseran ini mendorong transisi dari model transmisi informasi yang bersifat linier dan teknis menuju praktik persekutuan iman yang lebih relasional. Artikel ini mengkaji teologi komunikasi sebagai kerangka analisis untuk memahami kompleksitas pesan religius di ruang digital yang bersifat algoritmis dan terbuka. Melalui metode kajian pustaka konseptual teoretis, penelitian ini menunjukkan bahwa teologi komunikasi mampu melampaui keterbatasan teknis ilmu komunikasi konvensional dengan menempatkan pesan religius sebagai tindakan komunikatif yang sarat makna teologis, pengalaman spiritual, dan relasi. Kerangka ini memungkinkan analisis pesan religius mencakup penilaian terhadap integritas iman, tanggung jawab etis teologis, serta dampak transformatif komunikasi digital terhadap komunitas orang percaya. Dengan demikian, teologi komunikasi menawarkan keseimbangan antara kecanggihan teknologi digital dan kedalaman substansi iman sehingga komunikasi religius tetap relevan dan mampu menghadirkan persekutuan yang autentik.